(untitled) (Informatica, 2024)
The standardisation and accuracy of the starting movement will affect the athletes’ performance and the results of the game, and the differences in different sports, athletes’ physical qualities and coaches’ teaching methods make it difficult for the traditional correction of the starting movement to reflect a better application effect. Therefore, the study is based on the Openpose human posture estimation and recognition algorithm, which performs frame-posture relationship correlation analysis, continuity movement design and joint bone point repair to improve the accuracy of recognition. At the same time, taking into account the differences in the content of different assignments of posture data information, the study introduces a lightweight attention mechanism that focuses on temporal patterns on the basis of the recognition algorithm. The experimental results show that the recognition accuracy of the improved algorithm for the starting posture is above 0.85, and its recognition accuracy for the three phases of the starting action is above 93% compared with the Dynamic Time Warping (DTW) model and the High Resolution Human Keypoint Detection Network (HRNet-w48), with an F1 value of 0.6857, which is better than that of the DTW model (0.6857), and the F1 value of 0.6857. better than the DTW model (0.6214) and HRNet-w48 model (0.6321). The detection and recognition time of the improved algorithm for the starting movement is less than 0.1s, and it can better provide athletes with movement correction suggestions and formulate personalised training plans.